THE BALANCED SCORECARD METHOD FOR ASSESSING COMPANY PERFORMANCE (Case Study at PT Salatiga State Electricity Company) - Wikan Budi Utami; Iin Emy Prastiwi; Suhesti Ningsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to examine whether financial perspectives, customers, internal business processes, as well as perspectives of growth and learning partially or simultaneously affect the performance of PT Salatiga State Electricity Company (PLN). This study uses a quantitative descriptive approach with a population of employees of PT Perusahaan Listrik Negara (PLN) Salatiga. The sampling procedure used in this study is the purposive sampling method. This study uses a sample of 32 employees who fit predetermined criteria. Data in this study were collected by distributing questionnaires. The results of this study indicate that the financial perspective, customers, internal business processes as well as the perspective of growth and learning simultaneously have a significant effect on the performance of PT Salatiga State Electricity Company (PLN) as evidenced by the significance value of F (0.007) F table (2.71). Partially the variables of financial perspective, customer, and internal business process perspective have no significant effect on company performance, while the growth and learning perspective variable has a positive and significant effect on company performance. The adjusted R square determination coefficient is 0.309. This proves that the independent or independent variable is able to influence the dependent or dependent variable by 30.9%, while the remaining 69.1% is influenced by other variables outside this study. Keywords: balanced scorecard, company performance